The role of financial experience in driving investment decisions with financial knowledge as mediation variable - Setyawan, Surya; Tjiptodjojo, Kartika Imasari (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The layered financial burden in one's life usually becomes a chain that is difficult to break. The decision to be able to release the chain to the next generation is by how an individual must start thinking about being able to survive in retirement without having to provide financial burdens to their descendants. One option for the generation experiencing the financial burden is to invest early. The decision to invest must be based on experience and knowledge of good and adequate finance to minimize the risks that can occur. By minimizing the risks that may occur, it is hoped that it will increase awareness in individuals to be able to have better financial planning in the future. This study aims to examine how financial experience affects investment decisions through financial knowledge. The type of research used is explanatory research with a sample of 200 respondents who are individuals who have a double financial burden or sandwich generation and live in Bandung City. The results of the path analysis show that financial experience affects investment decisions through financial knowledge. Knowledge and information about the importance of financial management from an early age so that individuals who experience a double burden can break the chain as a sandwich generation is an implication in this study.